Design of a senolytic proteolysis targeting chimera against the B-cell lymphoma – extra large protein using in silico approaches - Pillay, Tahir S. (University of Pretoria, 2024)
Dissertation (MSc (Chemical Pathology))--University of Pretoria, 2020.